Structural, chemical and optical characterizations of an experimental SiO2-Y-TZP ceramic produced by the uniaxial/isostatic pressing technique - Mosquim, Victor (2019)
New glass ceramics enriched by polycrystalline materials has been produced by different processing methods. However, for these materials to be used as restorative dental materials in esthetical areas they must count with good optical properties, which are directly influenced by their structure and chemical composition. For these reasons, the aim of this study was to produce a new glass ceramic containing SiO2+Y-TZP via uniaxial/isostatic powder compression and to structurally and chemically characterize this material relating to its optical properties. SiO2 and Zpex® were used as starting powders. These two powders were mixed (97w%-3% ratio) and pressed in uniaxial (80MPa) and isostatic (206MPa) press and sintered at 1150ºC for 2h. The starting powders, the mixed powder (before sintering) and the sintered specimens were submitted to Scanning Electron Microscope/Energy Dispersive X-ray Spectroscopy (SEM/EDX), Transmission Electron Microscope (TEM), X-ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR). The materials density was measured. The contrast ratio and translucency parameter of the sintered specimen were compared to lithium disilicate (IPS e.max® CAD HT A1) and zirconia-reinforced lithium silicate (Celtra Duo® HT A1), using Kruskal-Wallis and post-hoc Dunn tests with a significance level set at 5%. Agglomerations of SiO2 and Zpex could be seen under SEM/EDX analysis due to their reduced particle size, yet, when sintered, some remaining porosities could be seen. The TEM analysis evidenced the spherical character of SiO2 grains and the crystallographic pattern of the Zpex particles. When mixed, Zpex can be seen inside the grain of SiO2. XDR analysis pointed out that SiO2 was amorphous, and Zpex presented monoclinic (m) and tetragonal (t) peaks. After sintering, crystallization of SiO2 can be seen without new m peaks. The FTIR spectra bands suggested an interaction between Si, O and Zr. The theoretical density value of the experimental ceramics was 1.663 g/cm3. The contrast ratio and the translucency parameter of the experimental ceramic were higher (p=0,000001) and lower (p=0,000001), respectively, than those of lithium disilicate and zirconia-reinforced lithium silicate. It can be concluded that the uniaxial/isostatic powder compression is an efficient method to obtain experimental ceramics for dental purposes and 1150ºC for 2h is sufficient to crystallize SiO2 without inducing t-m transformation of zirconia. Yet, this sintering protocol seems to be insufficient to densify the experimental ceramic, which may the reason for its lack of translucency.